An automated framework to support testing for process‐level race conditions. (10th May 2017) - Yu, Tingting; Srisa-an, Witty; Rothermel, Gregg
Summary: Race conditions are difficult to detect because they usually occur only under specific execution interleavings. Numerous program analysis and testing techniques have been proposed to detect race conditions between threads on single applications. However, most of these techniques neglect races that occur at the process level due to complex system event interactions. This article presents a framework, SIMEXPLORER, that allows engineers to effectively test for process‐level race conditions.SIMEXPLORER first uses dynamic analysis techniques to observe system execution, identify program locations of interest, and report faults related to oracles. Next, it uses virtualization to achieve the fine‐grained controllability needed to exercise event interleavings that are likely to expose races. We evaluated the effectiveness ofSIMEXPLORER on 24 real‐world applications containing both known and unknown process‐level race conditions. Our results show thatSIMEXPLORER is effective at detecting these race conditions, while incurring an overhead that is acceptable given its effectiveness improvements. Abstract : The SIMEXPLORER framework allows engineers to effectively test for process‐level race conditions. SIMEXPLORER first uses dynamic analysis techniques to observe system execution, identifies program locations of interest, and reports faults related to oracles. It then uses virtualization to achieve the fine‐grained controllability needed to exercise event interleavings that are likely to expose races.